Cultural Humility as a Spiritually Focused Intervention in Correctional Settings: The Role of Therapists' Multicultural Orientation. Issue 3 (September 2019) - Gafford, Jennifer; Raines, Tara C.; Sinha, Sree; DeBlaere, Cirleen; Davis, Don E.; Hook, Joshua N.; Owen, Jesse
The role of religion/spirituality (R/S) in the lives of incarcerated individuals is complex. Inmates may draw on R/S as a coping strategy, as a way to place responsibility, or as an approach to creating meaning. The importance of using R/S as a coping strategy can be amplified in the context of a correctional setting. While some attention has focused on the effectiveness of faith-based services in jails and prisons, very little emphasis has been placed on using those constructs in psychotherapy within the correctional context. Accordingly, this article explores the application of the multicultural orientation framework—including the important tenets of therapists' cultural humility, cultural comfort, and cultural opportunities—into psychotherapy practices with incarcerated individuals. In doing so, we will focus on how cultural humility can assist in addressing intersecting identities, including spirituality, race/ethnicity, socioeconomic status (SES), and gender identity to enhance the process and outcome of therapy. We will discuss how cultural humility can be effectively used to address common challenges for therapists when working with R/S issues in corrections and conclude with two case studies to illustrate the application.